PENGARUH PEMBERIAN TERAPI LATIHAN BERBASIS AIR TERHADAP KESEIMBANGAN PASIEN STROKE - Cicilia Hayuningrum; Danisa Nurul Fatimah; Martini Pisesi; Mutiara Lathifatul (Jurnal Ilmiah Fisioterapi, 2023)
Background: Stroke is a clinical sign that is rapidly developing as a result of impaired focal brain function accompanied by symptoms that last for more than 24 hours and can cause death. Problems that are often encountered in stroke patients include balance disorders, movement coordination, and disturbances in muscle strength. Hydrotherapy is a method of air that depends on the body's response. The application of hydrotherapy to stroke patients is beneficial for improving body balance, lowering blood pressure, and for body fitness. Purpose: To determine the effect of giving hydrotherapy exercises to the patient's stroke balance. Method: The method used in preparing this article is by searching articles through PubMed, Sage Journal, BMC. Result: The number of articles selected based on search results is 10. Conclusion: Providing hydrotherapy exercises to stroke patients can improve the patient's balance and coordination of movements